Comparing and Optimizing Nitrate Adsorption from Aqueous Solution Using Fe/Pt Bimetallic Nanoparticles and Anion Exchange Resins. (1st October 2015) - Daud, Muhammad; Khan, Zahiruddin; Ashgar, Aisha; Danish, M. Ihsan; Qazi, Ishtiaq A.
Abstract : This research work was carried out for the removal of nitrate from raw water for a drinking water supply. Nitrate is a widespread ground water contaminant. Methodology employed in this study included adsorption on metal based nanoparticles and ion exchange using anionic resins. Fe/Pt bimetallic nanoparticles were prepared in the laboratory, by the reduction of their respective salts using sodium borohydride. Scanning electron microscope, X-ray diffraction, energy dispersive spectrometry, and X-ray florescence techniques were utilized for characterization of bimetallic Fe/Pt nanoparticles. Optimum dose, pH, temperature, and contact time were determined for NO 3 - removal through batch tests, both for metal based nanoparticles and anionic exchange resin. Adsorption data fitted well the Langmuir isotherm and conformed to the pseudofirst-order kinetic model. Results indicated 97% reduction in nitrate by 0.25 mg/L of Fe/Pt nanoparticles at pH 7 and 83% reduction in nitrate was observed using 0.50 mg/L anionic exchange resins at pH 4 and contact time of one hour. Overall, Fe/Pt bimetallic nanoparticles demonstrated greater NO 3 - removal efficiency due to the small particle size, extremely large surface area (627 m 2 /g), and high adsorption capacity.